Perspektif Islam Terhadap Harta Simpanan (Tinjauan Fiqh) - Nurul Sultina (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2018)
Treasure is a human need in living the world, but not a few people who are competing to multiply the treasures, even people who are preoccupied by treasuressuch as abandoning religious dutiesbecause of neglecting to look for the treasure.Treasure is a core need in life where man will not be separated from it. The treasures of Islam are essentially belonging to Allah SWT. Then God has given it to man to take possession of the treasure. The Specificity of the ownerof an item according to syarakto act freely aims to take its benefits as long as there is no syar’i barrier. In Islam, deposit isjustified as long as not aimed to disobedience or boasting of wealth and abandonment of the remembrance of Allah. In Islamic law, the depositor is sacrificed to keep the property well, that is keeping the property so that it is not taken by others with no rights and keep the property from somethingthat are prohibited by religion. And also the depositors (owner)obliged to pay zakat from the property which he keeps every year and uses his treasures for the needs of the people when the people need help from it.